Peran Kualitas Produk dan Promosi terhadap Minat Beli Produk Coklat - Galieno, Reza; Rahmawati, Veronika; Mettan, Santho Vlennery (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
The current food and beverage business can open up potential opportunities, one of which is chocolate products. Processed chocolate products can be very diverse, from chocolate bars to drinks. In this study, the focus is on the consumption of chocolate in the form of bars. This study aimed to analyze the effect of product quality and promotion on consumer buying interest in chocolate. The research was conducted by distributing questionnaires to the general public who like chocolate. Questionnaires were distributed to 150 respondents, and a total of 131 respondents were eligible for further processing. The study used respondents with criteria 18 - 50 years, domiciled in the city of Surabaya, and chocolate lovers. This study uses multiple linear regression analysis based on the t-test, which can explain the effect of an independent variable on the dependent variable. From the study results, it can be concluded that there is an effect of product quality and promotion on consumer buying desired. Hence, managerial implications for chocolate producers to focus more on product quality improvement and innovation, as well as packaging that is attractive and can also improve the durability of chocolate.